Activating dealing in Islamic bonds in Algeria under the Islamic banking system - melak, saloua; boukhari, lahlou (Journal of Research in Finance and Accounting, 2021)
This research paper aims to study the possibility of activating Islamic sukuk in Algeria after the issuance of the Regulation 20-02 issued on March 24, 2020 related to Islamic banking in Algeria, given the prominent role Islamic financial products play in bringing about development at various economic or social levels The main objective of it is to propose a non-usurious financing alternative that meets the objectives of Islamic law according to specific Sharia controls. The Islamic products proposed by the above system, which include eight products, are contracts on the basis of which innovative products are created, the most important of which are Islamic bonds. Through this study, reference will be made to Algeria's experience in converting to Islamic banking, and to accelerate the process of adopting the issuance and circulation of Islamic sukuk due to its great role in achieving development. The study also concluded that the process of issuing sukuk in Algeria requires a set of legal and legislative controls to accommodate this type Of financing, which supports the various agricultural, industrial, commercial and service sectors, in addition to stimulating and revitalizing the role of the Algiers Stock Exchange, and the most appropriate Islamic instruments to finance major projects in various sectors, in addition to its distinctive role in providing liquidity and addressing the budget deficit and attracting a large segment of investors Wanting to avoid forbidden transactions.